Preparation method of high-strength modified PA6 composite material
By preparing high-strength modified PA6 composite materials, using materials such as PA6 resin, PA10T resin and filler composition, combined with twin-screw extrusion, granulation, injection molding and heat treatment, the problems of dimensional instability and poor mechanical properties caused by high water absorption of nylon 6 products are solved, and the effects of high strength, dimensional stability and impact toughness are achieved, expanding the application range and reducing production costs.
Patent Information
- Application Number
- CN202411853285.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
During use, the nylon 6 product is easily formed with hydrogen bonds with water molecules in the environment due to the strong polarity of amide groups in the polyamide molecular chain, resulting in a large water absorption rate of nylon 6, affecting the dimensional stability and mechanical properties of the product.
By adopting a high-strength modified PA6 composite material, a high-strength modified PA6 composite material is prepared by mixing 40-65 parts by weight of PA6 resin, 15-25 parts by weight of PA10T resin, 15-35 parts by weight of filler composition, 0.5-2 parts by weight of antioxidant, 0.5-2 parts by weight of anti-ultraviolet aging additive, 0.5-3 parts by weight of lubricant, and 0.5-2 parts by weight of coupling agent, and a high-strength modified PA6 composite material is prepared by the steps of twin screw extrusion, granulation, injection molding and heat treatment.
The prepared modified PA6 composite material has good mechanical strength, dimensional stability and impact toughness, expanding the application range of nylon 6 products, while reducing production costs and realizing industrial manufacturing.
Smart Images

Figure BDA0005191120360000151 
Figure BDA0005191120360000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon composite material preparation, and in particular to a method for preparing a high-strength modified PA6 composite material. Background Art
[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeating amide groups -[NHCO]- on the main chain of the molecule. Nylon 6 is the earliest developed variety of engineering plastics and is also one of the varieties with the largest output of polyamide plastics. Nylon has the advantages of thermoplasticity, light weight, good toughness, good chemical resistance and durability, wear resistance, and heat resistance. It is widely used in the automotive industry, electronic and electrical industry, mechanical parts, automobiles, aviation and other fields. However, nylon 6 also has the following defects: during use, due to the strong polarity of the amide group in the polyamide molecular chain, it is easy to form hydrogen bonds with water molecules in the environment, resulting in a large water absorption rate of nylon 6, which affects the dimensional stability and mechanical properties of nylon 6 products, and limits the application and development of nylon 6 products. In order to broaden the application scope of nylon 6, the inventor provides a method for preparing a high-strength modified PA6 composite material. Summary of the invention
[0003] In order to solve the problems of mechanical property deviation and poor dimensional stability of nylon 6 products in the prior art, the present invention provides a method for preparing a high-strength modified PA6 composite material.
[0004] The present invention provides a method for preparing a high-strength modified PA6 composite material, which is achieved through the following technical solutions:
[0005] A method for preparing a high-strength modified PA6 composite material, wherein the high-strength modified PA6 composite material is prepared from 40-65 parts by weight of PA6 resin, 15-25 parts by weight of PA10T resin, 15-35 parts by weight of a filler composition, 0.5-2 parts by weight of an antioxidant, 0.5-2 parts by weight of an anti-ultraviolet aging additive, 0.5-3 parts by weight of a lubricant, and 0.5-2 parts by weight of a coupling agent;
[0006] The filler composition is composed of chopped glass fibers with nano-carbon grafted on the surface and inorganic whiskers with nano-carbon grafted on the surface; the mass ratio of the chopped glass fibers with nano-carbon grafted on the surface to the inorganic whiskers with nano-carbon grafted on the surface is (80-95):(5-20);
[0007] The preparation method of the high-strength modified PA6 composite material comprises the following steps:
[0008] Step 1, preparation of filler composition, and drying PA6 resin and PA10T resin separately at the same time;
[0009] Step 2, uniformly mixing the accurately measured PA6 resin, PA10T resin, filler composition, antioxidant, anti-ultraviolet aging additive, lubricant, and coupling agent to obtain a mixture;
[0010] Step 3, the mixture obtained in step 2 is placed in a twin-screw extruder for melt extrusion, the machining temperature is 260-290° C., the twin-screw speed is 100-160 rpm, the molten extrudate is drawn and cooled, and then input into a granulator for pelletizing, the pelletizing speed of the granulator is 350-400 rpm, and a high-strength modified PA6 composite masterbatch can be obtained;
[0011] Step 4: After vacuum drying, the high-strength modified PA6 composite masterbatch in step 3 is input into an injection molding machine, the injection molding temperature is 260-285°C, the twin screw speed is 160-200rpm, the injection molding pressure is 75-100MPa, and the molten extrudate of the injection molding machine is injected into a molding mold with a mold temperature of 75-80°C, the pressure is maintained for 15-30s, and the semi-finished high-strength modified PA6 composite material of a predetermined shape is obtained by cooling;
[0012] Step 5: heat-treating the semi-finished high-strength modified PA6 composite material. The heat treatment parameters are as follows: heat-treating at 110-135° C. for 20-35 minutes, and cooling to room temperature to obtain a finished high-strength modified PA6 composite material.
[0013] The modified PA6 composite material prepared in the present invention has good mechanical strength, dimensional stability and good impact toughness, which expands the application range of nylon 6 products. In addition, the preparation method of the present invention is relatively simple, has low operation difficulty, is easy to realize industrial production and manufacturing, and reduces the production cost of nylon 6 products.
[0014] Preferably, the high-strength modified PA6 composite material is made of 48-50 parts by weight of PA6 resin, 22-25 parts by weight of PA10T resin, 24-26 parts by weight of filler composition, 0.8-1.2 parts by weight of antioxidant, 0.5-1.2 parts by weight of anti-ultraviolet aging additive, 0.8-1.6 parts by weight of lubricant, and 1.0-1.5 parts by weight of coupling agent.
[0015] By adopting the above technical solutions, the modified PA6 composite material is given good mechanical strength, dimensional stability, and good impact toughness, while optimizing production costs and improving core production competitiveness.
[0016] Preferably, the chopped glass fiber with surface grafted nanocarbon includes chopped glass fiber as a carrier, the length of the chopped glass fiber is 0.5-3mm, and the surface of the chopped glass fiber is grafted with at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nanocarbon fibers by in-situ sintering of nanometals.
[0017] Preferably, the inorganic whiskers with surface grafted nanocarbon include inorganic whiskers as carriers, the length of the inorganic whiskers is 0.5-30 μm, and the surfaces of the inorganic whiskers are grafted with at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nano-carbon fibers by in-situ sintering of nanometals.
[0018] Preferably, the inorganic whisker is at least one of zinc oxide whisker, zirconium oxide whisker and aluminum oxide whisker.
[0019] Preferably, the chopped glass fibers with nano-carbon grafted on the surface are compounded by chopped glass fibers with multi-walled carbon nanotubes grafted on the surface and chopped glass fibers with graphene grafted on the surface in a mass ratio of 100:(50-200).
[0020] Preferably, the inorganic whiskers with nano-carbon grafted on the surface are compounded by inorganic whiskers with multi-walled carbon nanotube grafted on the surface and inorganic whiskers with graphene grafted on the surface in a mass ratio of 100:(50-200).
[0021] Preferably, the filler composition is made of the following raw materials in percentage by mass: 30-45wt% of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 50-60wt% of chopped glass fibers with graphene grafted on the surface, 3-6wt% of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and 2-4wt% of inorganic whiskers with graphene grafted on the surface.
[0022] By adopting the above technical solutions, the overall mechanical strength, impact toughness and dimensional stability of the high-strength modified PA6 composite material can be improved.
[0023] Preferably, the antioxidant is composed of nano silicon nitride, antioxidant 1010, and antioxidant 168; the anti-ultraviolet aging additive is at least one of UV-234, UV-622, UV-1130, UV-292, and UV-123; and the lubricant is at least one of polytetrafluoroethylene powder, molybdenum disulfide, and flake graphite.
[0024] By adopting the above technical solution, the overall weather resistance and processing performance can be improved.
[0025] Preferably, the coupling agent is at least one of isocyanate silane, epoxy silane and titanate coupling agent.
[0026] Preferably, the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane and tri(dioctylpyrophosphate)titanate isopropyl in a mass ratio of 100:(10-25).
[0027] By adopting the above technical solution, the filler composition can be dispersed more evenly inside the matrix resin, thereby improving the overall mechanical strength, impact toughness and dimensional stability.
[0028] In summary, the present invention has the following advantages:
[0029] 1. The modified PA6 composite material prepared in the present invention has good mechanical strength, dimensional stability and good impact toughness, which expands the application range of nylon 6 products.
[0030] 2. The equipment used in the preparation method provided by the present invention is relatively conventional, the equipment investment cost is relatively low, and the operating technology of the required equipment is mature, which reduces the overall processing difficulty and facilitates the realization of the purpose of industrialized manufacturing.
[0031] 3. The coupling agent is optimized and designed in the present invention to match the filler composition with an optimized ratio, so that the filler composition can be more evenly dispersed in the nylon resin system. The nano-carbon grafted on the chopped glass fiber and the nano-carbon grafted on the inorganic whisker overcome the problem of low compatibility and uneven dispersion with the nylon resin matrix, and the nano-carbon can be evenly dispersed in the nylon resin system, which greatly enhances the tensile strength, yield strength, impact toughness of the modified PA6 composite material, and improves the heat resistance and dimensional stability. DETAILED DESCRIPTION
[0032] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0033] Example
[0034] A high-strength modified PA6 composite material is prepared from 40-65 parts by weight of PA6 resin (Toray CM1007, Japan), 18-25 parts by weight of PA10T resin (polydecane terephthalamide, semi-aromatic nylon, Kingfa Technology Co., Ltd.), 15-35 parts by weight of a filler composition, 0.5-2 parts by weight of an antioxidant, 0.5-2 parts by weight of an anti-ultraviolet aging additive, 0.5-3 parts by weight of a lubricant, and 0.5-2 parts by weight of a coupling agent.
[0035] Preferably, the high-strength modified PA6 composite material is made of 48-50 parts by weight of PA6 resin, 22-25 parts by weight of PA10T resin, 24-26 parts by weight of filler composition, 0.8-1.2 parts by weight of antioxidant, 0.5-1.2 parts by weight of anti-ultraviolet aging additive, 0.8-1.6 parts by weight of lubricant, and 1.0-1.5 parts by weight of coupling agent.
[0036] The antioxidant is composed of nano silicon nitride, antioxidant 1010 and antioxidant 168, and the mass ratio of nano silicon nitride, antioxidant 1010 and antioxidant 168 is 20:75:5.
[0037] The anti-ultraviolet aging aid is at least one of UV-234, UV-622, UV-1130, UV-292 and UV-123. Preferably, the anti-ultraviolet aging aid is UV-622, UV-1130 and UV-292. UV-622 and the anti-ultraviolet aging aid are composed of UV-622, UV-1130 and UV-292 in a mass ratio of 30:60:10.
[0038] The lubricant is at least one of polytetrafluoroethylene powder, molybdenum disulfide, and flake graphite. Preferably, the lubricant is molybdenum disulfide, which can play a lubricating role and improve wear resistance and flame retardancy.
[0039] The coupling agent is at least one of isocyanatosilane, epoxysilane and titanate coupling agent. Preferably, the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane and tri(dioctylpyrophosphate)titanate isopropyl in a mass ratio of 100:(10-25).
[0040] The filler composition is composed of short glass fibers with nano-carbon grafted on the surface and inorganic whiskers with nano-carbon grafted on the surface in a mass ratio of (80-95):(5-20).
[0041] The chopped glass fiber with surface grafted nanocarbon includes chopped glass fiber as a carrier, the length of the chopped glass fiber is 0.5-3mm, and at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nanocarbon fibers is grafted on the surface of the chopped glass fiber by in-situ sintering of nanometal.
[0042] Preferably, the chopped glass fibers with nano-carbon grafted on the surface are compounded by chopped glass fibers with multi-walled carbon nanotubes grafted on the surface and chopped glass fibers with graphene grafted on the surface in a mass ratio of 100:(50-200).
[0043] The inorganic whiskers with nano-carbon grafted on the surface include inorganic whiskers as carriers, the length of the inorganic whiskers is 0.5-30 μm, and the inorganic whiskers are at least one of zinc oxide whiskers, zirconium oxide whiskers, and aluminum oxide whiskers. At least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nano-carbon fibers is grafted on the surface of the inorganic whiskers by in-situ sintering of nano-metals.
[0044] Preferably, the inorganic whiskers with nano-carbon grafted on the surface are prepared by compounding the inorganic whiskers with multi-walled carbon nanotube grafted on the surface and the inorganic whiskers with graphene grafted on the surface in a mass ratio of 100:(50-200).
[0045] Further preferably, the filler composition is made of the following raw materials in percentage by mass: 30-45wt% of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 50-60wt% of chopped glass fibers with graphene grafted on the surface, 3-6wt% of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and 2-4wt% of inorganic whiskers with graphene grafted on the surface.
[0046] A method for preparing a high-strength modified PA6 composite material comprises the following steps:
[0047] Step 1, preparation of a filler composition, namely, respectively preparing chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, chopped glass fibers with graphene grafted on the surface, inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and inorganic whiskers with graphene grafted on the surface, mixing the prepared chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, chopped glass fibers with graphene grafted on the surface, inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and inorganic whiskers with graphene grafted on the surface in a ratio, and then performing dry kneading treatment with a coupling agent to obtain a finished filler composition;
[0048] At the same time, PA6 resin and PA10T resin were dried separately, and the specific drying parameters were drying at 110°C for 12 hours;
[0049] Step 2: According to the formula, the PA6 resin and PA10T resin dried in step 1, the finished filler composition in step 1, the antioxidant, the anti-ultraviolet aging additive, and the lubricant are accurately weighed and placed in a high-speed dispersion kettle, and high-speed dispersion treatment is performed for 2-4 hours under nitrogen protection, and the mixture is fully mixed to obtain a mixture;
[0050] Step 3, the mixture obtained in step 2 is placed in a twin-screw extruder for melt extrusion, the machining temperature is 260-290° C., the twin-screw speed is 100-160 rpm, the molten extrudate is drawn and cooled, and then input into a granulator for pelletizing, the pelletizing speed of the granulator is 350-400 rpm, and a high-strength modified PA6 composite masterbatch can be obtained, and the particle size of the obtained high-strength modified PA6 composite masterbatch is between 2.0-3.0 mm;
[0051] Step 4: The high-strength modified PA6 composite masterbatch in step 3 is placed in a vacuum drying oven, evacuated to 10Pa and vacuum dried at 105°C for 6h. The high-strength modified PA6 composite masterbatch after vacuum drying is input into an injection molding machine for injection molding. The injection molding temperature is 260-285°C, the twin-screw speed is 160-200rpm, and the molten extrudate discharged from the die head of the injection molding machine is injected into a molding mold with a mold temperature of 75-80°C at an injection pressure of 75-100MPa, and the pressure is maintained for 15-30s at a holding pressure of 30-50MPa, and cooled to below 60°C at a cooling pressure of 10-25MPa, so as to obtain a semi-finished high-strength modified PA6 composite material of a predetermined shape;
[0052] Step 5: heat-treating the semi-finished high-strength modified PA6 composite material. The heat treatment parameters are as follows: heat-treating at 110-135° C. for 20-35 minutes, and cooling to room temperature to obtain a finished high-strength modified PA6 composite material.
[0053] Preparation Example 1: The preparation method of chopped glass fiber with multi-walled carbon nanotubes grafted on the surface is as follows:
[0054] Step 1: At room temperature, add 0.04 mol of 2-ethyl-4-methylimidazole 2E4MI and 0.02 mol of silver acetate AgAc into 1000 mL of dichloromethane, stir magnetically at a speed of 240 r / min until the AgAc particles completely disappear, and obtain a clear and transparent Ag(2E4MI)2Ac complex solution;
[0055] Step 2: Add 1g of CNTs (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, Industrial-grade multi-walled carbon nanotubes IMWCNTs, model TNIMH8) and 1g of PVP (polyvinyl pyrrolidone, K30, Shanghai McLean Biochemical Technology Co., Ltd.) to the Ag(2E4MI)2Ac complex solution, use ultrasonic dispersion (ultrasonic generator power 1200W, frequency 20kHz) for 3 hours, add 100g of chopped glass fiber (fiber diameter: 6-9μm, refractive index: 1.54, product hardness: 7H, fiber density: 2.2T / cubic, product shape: fibrous, tensile strength: 1950mpa, length 3mm, customized by Shijiazhuang Super Micro New Material Technology Co., Ltd.), continue ultrasonic dispersion for 30min to obtain a dispersion;
[0056] Step 3: The dispersion obtained in step 2 is subjected to reduced pressure distillation treatment, and the dichloromethane in the dispersion is removed, and the solid is subjected to high-temperature sintering treatment. The high-temperature sintering temperature is controlled at 210°C, and the high-temperature sintering time is 4 hours. The obtained solid is placed in a three-roll mill for 3 times of grinding and crushing, and the roller spacing of the three-roll mill is 80 μm. The obtained powder is added to 500 mL of ethanol and stirred evenly, and then poured into a basket grinder for grinding, grinding at a speed of 2000 r / min for 30 minutes, and then filtered and dried to obtain the finished product.
[0057] Preparation Example 2: Preparation Example 2 is to prepare chopped glass fibers with surface grafted graphene, and its steps are basically the same as the preparation method of chopped glass fibers with surface grafted multi-walled carbon nanotubes in Preparation 1, except that: Step 2: 1g of graphene (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, Industrial Grade Graphene TNIRGO) and 1g of PVP (polyvinyl pyrrolidone, K30, Shanghai McLean Biochemical Technology Co., Ltd.) are added to the Ag (2E4MI) 2Ac complex solution, and ultrasonic dispersion (ultrasonic generator power 1200W, frequency 20kHz) is used for 3 hours, and 100 grams of chopped glass fibers (fiber diameter: 6-9μm, refractive index: 1.54, product hardness: 7H, fiber density: 2.2T / cubic, product shape: fibrous, tensile strength: 1950mpa, length 3mm, customized by Shijiazhuang Super Micro New Materials Technology Co., Ltd.) are added, and ultrasonic dispersion is continued for 30min to obtain a dispersion. The remaining steps are the same as Preparation Example 1.
[0058] Preparation Example 3: Preparation Example 3 is to prepare inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and its preparation method is basically the same as the preparation method of short glass fibers with multi-walled carbon nanotubes grafted on the surface. The difference is: Step 2: Add 1g of CNTs (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, Industrial-grade multi-walled carbon nanotubes IMWCNTs, model TNIMH8) and 1g of PVP (polyvinyl pyrrolidone, K30, Shanghai McLean Biochemical Technology Co., Ltd.) to the Ag (2E4MI) 2Ac complex solution, use ultrasonic dispersion (ultrasonic generator power 1200W, frequency 20kHz) for 3 hours, add 100 grams of alumina whiskers (diameter: 0.5-1um, length: 10um, aspect ratio: 15, purity: 99.9%, customized by Hubei Xinyuhong Biomedical Technology Co., Ltd.), continue ultrasonic dispersion for 30min, and obtain a dispersion. The remaining steps are the same as those of Preparation Example 1.
[0059] Preparation Example 4: Preparation Example 4 is to prepare inorganic whiskers with surface grafted graphene, and its preparation method is basically the same as the preparation method of short glass fibers with surface grafted graphene. The difference is: Step 2: Add 1g of graphene (Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, Industrial Grade Graphene TNIRGO) and 1g of PVP (polyvinyl pyrrolidone, K30, Shanghai McLean Biochemical Technology Co., Ltd.) to the Ag (2E4MI) 2Ac complex solution, use ultrasonic dispersion (ultrasonic generator power 1200W, frequency 20kHz) for 3 hours, add 100 grams of alumina whiskers (diameter: 0.5-1um, length: 10um, aspect ratio: 15, purity: 99.9%, customized by Hubei Xinyuhong Biomedical Technology Co., Ltd.), continue ultrasonic dispersion for 30min, and obtain a dispersion. The remaining steps are the same as those of Preparation Example 1.
[0060] Example 1: A high-strength modified PA6 composite material consists of 55 parts of PA6 resin, 25 parts of PA10T resin, 8 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 7.2 parts of chopped glass fibers with surface grafted graphene, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0061] A method for preparing a high-strength modified PA6 composite material comprises the following steps:
[0062] Step 1, preparation of a filler composition, namely, preparing short glass fibers with multi-walled carbon nanotubes grafted on the surface (see Preparation Example 1), short glass fibers with graphene grafted on the surface (see Preparation Example 2), inorganic whiskers with multi-walled carbon nanotubes grafted on the surface (see Preparation Example 3), and inorganic whiskers with graphene grafted on the surface (see Preparation Example 4);
[0063] 240 g of the prepared chopped glass fiber with multi-walled carbon nanotubes grafted on the surface, 216 g of the chopped glass fiber with graphene grafted on the surface, 14.4 g of the inorganic whisker with multi-walled carbon nanotubes grafted on the surface, and 9.6 g of the inorganic whisker with graphene grafted on the surface were placed in a high-speed stirring kettle and mixed at 400 rpm for 15 min. After being evenly mixed, 30 g of γ-glycidyloxypropyltrimethoxysilane and 6 g of tri(dioctylpyrophosphate)titanate isopropyl were dry-kneaded for 30 min to obtain a finished filler composition;
[0064] At the same time, PA6 resin and PA10T resin were dried separately, and the specific drying parameters were drying at 110°C for 12 hours;
[0065] Step 2, according to the formula, accurately weigh 1650g of the PA6 resin that has been dried in step 1, 750g of the PA10T resin, 516g of the finished filler composition in step 1, 7.2g of nano silicon nitride, 27g of antioxidant 1010, 1.8g of antioxidant 168, 24g of molybdenum disulfide, 7.2g of UV-622, 14.4g of UV-11302, and 2.4g of UV-292, place them in a high-speed dispersing kettle, mix them at 400rpm for 2.0h under nitrogen protection, and mix them thoroughly to obtain a mixture;
[0066] Step three, the obtained mixture in step two is placed in a twin-screw extruder for melt extrusion, the machining temperature is 260-290°C, the extrusion processing temperature is divided into five sections, the first extrusion processing temperature zone is set at 260°C, the second extrusion processing temperature zone is set at 275°C, the third extrusion processing temperature zone is set at 285°C, the fourth extrusion processing temperature zone is set at 290°C, the fifth extrusion processing temperature zone is set at 290°C, the twin-screw speed is 124rpm, the molten extrudate is drawn and cooled, and then input into a granulator for pelletizing treatment, the cutting speed of the granulator is 360rpm, and a high-strength modified PA6 composite masterbatch can be obtained, and the particle size of the obtained high-strength modified PA6 composite masterbatch is between 2.0-2.4mm;
[0067] Step 4: The high-strength modified PA6 composite masterbatch in step 3 is placed in a vacuum drying oven, evacuated to 10Pa and vacuum dried at 105°C for 6h. The high-strength modified PA6 composite masterbatch after vacuum drying is input into an injection molding machine for injection molding. The injection molding temperature is 260-285°C. The extrusion processing temperature of the injection molding machine is divided into seven sections. The first extrusion processing temperature zone is set at 260°C, the second extrusion processing temperature zone is set at 270°C, the third extrusion processing temperature zone is set at 275°C, and the fourth extrusion processing temperature zone is set at 285°C. The temperature of the temperature zone is set at 280°C, the temperature of the fifth extrusion processing temperature zone is set at 285°C, the temperature of the sixth extrusion processing temperature zone is set at 285°C, the temperature of the seventh extrusion processing temperature zone is set at 285°C, the speed of the twin screw is 165rpm, the molten extrudate discharged from the die head of the injection molding machine is injected into the molding mold with a mold temperature of 80°C at an injection pressure of 80MPa, the pressure is maintained at a holding pressure of 40MPa for 30s, and the temperature is cooled to below 60°C at a cooling pressure of 20MPa, so as to obtain a semi-finished high-strength modified PA6 composite material of a predetermined shape;
[0068] Step 5: heat-treating the semi-finished high-strength modified PA6 composite material. The heat treatment parameters are as follows: heat-treating at 125° C. for 30 minutes, and cooling to room temperature to obtain a finished high-strength modified PA6 composite material.
[0069] The difference between Example 2 and Example 1 is that a high-strength modified PA6 composite material consists of 60 parts of PA6 resin, 20 parts of PA10T resin, 8 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 7.2 parts of chopped glass fibers with surface grafted graphene, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0070] The difference between Example 3 and Example 1 is that a high-strength modified PA6 composite material is composed of 65 parts of PA6 resin, 15 parts of PA10T resin, 8 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 7.2 parts of chopped glass fibers with surface grafted graphene, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0071] The difference between Example 4 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 12 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 10.8 parts of chopped glass fibers with surface grafted graphene, 0.72 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.48 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0072] The difference between Example 5 and Example 1 is that a high-strength modified PA6 composite material is composed of 52.8 parts of PA6 resin, 13.2 parts of PA10T resin, 15 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 13.5 parts of chopped glass fibers with surface grafted graphene, 0.9 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.60 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0073] The difference between Example 6 and Example 1 is that a high-strength modified PA6 composite material is composed of 48.8 parts of PA6 resin, 17.5 parts of PA10T resin, 15.75 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 1.05 parts of chopped glass fibers with surface grafted graphene, 0.70 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0074] The difference between Example 7 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 22.8 parts of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 0 parts of chopped glass fibers with graphene grafted on the surface, 1.2 parts of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, 0 parts of inorganic whiskers with graphene grafted on the surface, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0075] The difference between Example 8 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 22.8 parts of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 0 parts of chopped glass fibers with graphene grafted on the surface, 0 parts of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, 1.2 parts of inorganic whiskers with graphene grafted on the surface, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0076] The difference between Example 9 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 0 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 22.8 parts of chopped glass fibers with surface grafted graphene, 1.2 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0077] The difference between Example 10 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 0 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 22.8 parts of chopped glass fibers with surface grafted graphene, 0 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 1.2 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0078] The difference between Example 11 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 21.6 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 2.4 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0079] The difference between Example 12 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 19.2 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 4.8 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0080] The difference between Example 13 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 12 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 10.8 parts of chopped glass fibers with surface grafted graphene, 0.72 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.48 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, and 1.2 parts of γ-glycidyloxypropyltrimethoxysilane.
[0081] The difference between Example 14 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 12 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 10.8 parts of chopped glass fibers with surface grafted graphene, 0.72 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.48 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, and 1.2 parts of 3-isocyanatepropyltriethoxysilane.
[0082] The difference between Comparative Example 1 and Example 1 is that the high-strength modified PA6 composite material is composed of 80 parts of PA6 resin, 8 parts of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 7.2 parts of chopped glass fibers with graphene grafted on the surface, 0.48 parts of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, 0.32 parts of inorganic whiskers with graphene grafted on the surface, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0083] The difference between Comparative Example 2 and Example 1 is that the high-strength modified PA6 composite material is composed of 70 parts of PA6 resin, 10 parts of PA10T resin, 8 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 7.2 parts of chopped glass fibers with surface grafted graphene, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0084] The difference between Comparative Example 3 and Example 1 is that the high-strength modified PA6 composite material is composed of 50 parts of PA6 resin, 30 parts of PA10T resin, 8 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 7.2 parts of chopped glass fibers with surface grafted graphene, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.32 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0085] The difference between Comparative Example 4 and Example 1 is that a high-strength modified PA6 composite material is composed of 68.8 parts of PA6 resin, 17.2 parts of PA10T resin, 5.25 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 4.725 parts of chopped glass fibers with surface grafted graphene, 0.315 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.21 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0086] The difference between Comparative Example 5 and Example 1 is that a high-strength modified PA6 composite material is composed of 44.8 parts of PA6 resin, 11.2 parts of PA10T resin, 6.125 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 5.5125 parts of chopped glass fibers with surface grafted graphene, 0.3675 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.245 parts of inorganic whiskers with surface grafted graphene, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0087] The difference between Comparative Example 6 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 24 parts of chopped glass fiber (fiber diameter: 6-9 μm, refractive index: 1.54, product hardness: 7H, fiber density: 2.2T / cubic, product shape: fibrous, tensile strength: 1950 MPa, length 3 mm, customized by Shijiazhuang Super Micro New Material Technology Co., Ltd.), 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tris(dioctyl pyrophosphate)titanate isopropyl ester.
[0088] The difference between Comparative Example 7 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 24 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0089] The difference between Comparative Example 8 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 24 parts of chopped glass fibers with surface grafted graphene, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0090] The difference between Comparative Example 9 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 23.52 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 0.48 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.24 parts of nano silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0091] The difference between Comparative Example 10 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 18 parts of chopped glass fibers with surface grafted multi-walled carbon nanotubes, 6 parts of inorganic whiskers with surface grafted multi-walled carbon nanotubes, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0092] The difference between Comparative Example 11 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 22.8 parts of chopped glass fibers, 1.2 parts of inorganic whiskers, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctyl pyrophosphate) isopropyl titanate.
[0093] The difference between Comparative Example 12 and Example 1 is that a high-strength modified PA6 composite material is composed of 57.6 parts of PA6 resin, 14.4 parts of PA10T resin, 22.8 parts of chopped glass fibers, 1.2 parts of inorganic whiskers, 0.24 parts of multi-walled carbon nanotubes, 0.24 parts of graphene, 0.24 parts of nano-silicon nitride, 0.9 parts of antioxidant 1010, 0.06 parts of antioxidant 168, 0.8 parts of molybdenum disulfide, 0.24 parts of UV-622, 0.48 parts of UV-11302, 0.08 parts of UV-292, 1 part of γ-glycidyloxypropyltrimethoxysilane, and 0.2 parts of tri(dioctylpyrophosphate)titanate isopropyl.
[0094] The control group was a commercially available 30wt% glass fiber modified nylon 6 resin material, an injection molding grade glass fiber reinforced nylon PA6 material from Suzhou New District Huashida Engineering Plastics Co., Ltd.
[0095] Performance testing
[0096] 1. Tensile strength: According to GB / T 1040-2018 "Test method for tensile properties of plastics", the tensile strength of nylon composite materials was measured at a temperature of 23°C and a tensile rate of 20 mm / min.
[0097] 2. Bending properties: According to GB / T 9341-2008 "Determination of flexural properties of plastics", the tensile strength of nylon composite materials was measured at a temperature of 23°C and a rate of 2 mm / min.
[0098] 3. Impact toughness: According to GB / T 1043-2008, V-notch specimens were used to measure the simply supported beam notched impact strength of nylon composite materials at a temperature of 23°C and a pendulum of 5.5J.
[0099] 4. Absorption performance determination method: first place the high-strength modified PA6 composite masterbatch in a vacuum drying oven, evacuate to 10Pa and vacuum dry at 105°C for 6 hours, weigh and record it as m1, soak the vacuum-dried high-strength modified PA6 composite masterbatch in deionized water at 23°C for 24 hours, wipe the surface moisture with cotton cloth and weigh it as m2. The water absorption rate is calculated as follows: ω = (m2-m1)*100 / m1.
[0100] Data analysis
[0101] Table 1: Test parameters of high-strength modified PA6 composite materials in Examples 1-14 and Comparative Examples 1-12
[0102]
[0103]
[0104] It can be seen from Examples 1-3 and Comparative Examples 1-3 and Table 1 that when PA10T resin and PA6 resin are mixed and compounded and the mass ratio of PA10T resin to PA6 resin is controlled to be (55-65):(15-25), the mechanical properties, dimensional stability and impact resistance of the prepared PA6 composite material are relatively excellent.
[0105] From Examples 2, 4-6 and Comparative Examples 4-5 and Table 1, it can be seen that the amount of the filler composition added is preferably 15-35wt%. When the filler exceeds about 25wt%, although the tensile strength and flexural strength are improved, the impact toughness is on a downward trend. Considering the mechanical properties and impact toughness, the amount of the filler composition added is preferably 24-26wt%.
[0106] It can be seen from Examples 2, 4-6 and Comparative Examples 4-5 and Table 1 that the filler composition composed of chopped glass fibers with surface grafted nano-carbon and inorganic whiskers with surface grafted nano-carbon prepared in the present invention can effectively improve the mechanical properties and impact toughness of the modified PA6 composite material.
[0107] It can be seen from Examples 4, 7-12 and Comparative Examples 6-12 and Table 1 that the mass ratio of the chopped glass fiber grafted with nano-carbon on the surface to the inorganic whisker grafted with nano-carbon on the surface is (80-95): (5-20) The filler composition can effectively improve the mechanical properties and impact toughness of the modified PA6 composite material. Preferably, the filler composition composed of 30-45wt% of chopped glass fiber grafted with multi-walled carbon nanotubes on the surface, 50-60wt% of chopped glass fiber grafted with graphene on the surface, 3-6wt% of inorganic whisker grafted with multi-walled carbon nanotubes on the surface, and 2-4wt% of inorganic whisker grafted with graphene on the surface can effectively ensure the mechanical properties and impact toughness of the modified PA6 composite material, while reducing the overall production cost, which is beneficial to the lightweight of PA6 nylon material.
[0108] It can be seen from Example 1 and Examples 13-14 and Table 1 that the use of a coupling agent consisting of γ-glycidyloxypropyltrimethoxysilane and tri(dioctylpyrophosphate)titanate isopropyl in a mass ratio of 100:(10-25) can improve the uniform dispersion of the filler composition, thereby improving the mechanical properties and impact toughness of the modified PA6 composite material, and expanding the application range of nylon 6 products.
[0109] In summary, the modified PA6 composite material prepared in the present invention has good mechanical strength, dimensional stability and good impact toughness, which expands the application range of nylon 6 products.
[0110] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a high-strength modified PA6 composite material, characterized in that: The high-strength modified PA6 composite material is made of 40-65 parts by weight of PA6 resin, 15-25 parts by weight of PA10T resin, 15-35 parts by weight of filler composition, 0.5-2 parts by weight of antioxidant, 0.5-2 parts by weight of anti-ultraviolet aging additive, 0.5-3 parts by weight of lubricant, and 0.5-2 parts by weight of coupling agent; The filler composition is composed of chopped glass fibers with nano-carbon grafted on the surface and inorganic whiskers with nano-carbon grafted on the surface; the mass ratio of the chopped glass fibers with nano-carbon grafted on the surface to the inorganic whiskers with nano-carbon grafted on the surface is (80-95):(5-20); The preparation method of the high-strength modified PA6 composite material comprises the following steps: Step 1, preparation of a filler composition, and drying of PA6 resin and PA10T resin respectively; Step 2, uniformly mixing the accurately measured PA6 resin, PA10T resin, filler composition, antioxidant, anti-ultraviolet aging additive, lubricant, and coupling agent to obtain a mixture; Step 3, the mixture obtained in step 2 is placed in a twin-screw extruder for melt extrusion, the machining temperature is 260-290° C., the twin-screw speed is 100-160 rpm, the molten extrudate is drawn and cooled, and then input into a granulator for pelletizing, the pelletizing speed of the granulator is 350-400 rpm, and a high-strength modified PA6 composite masterbatch can be obtained; Step 4: After vacuum drying, the high-strength modified PA6 composite masterbatch in step 3 is input into an injection molding machine, the injection molding temperature is 260-285°C, the twin screw speed is 160-200rpm, the injection molding pressure is 75-100MPa, and the molten extrudate of the injection molding machine is injected into a molding mold with a mold temperature of 75-80°C, the pressure is maintained for 15-30s, and the semi-finished high-strength modified PA6 composite material of a predetermined shape is obtained by cooling; Step 5: heat-treating the semi-finished high-strength modified PA6 composite material. The heat treatment parameters are as follows: heat-treating at 110-135° C. for 20-35 minutes, and cooling to room temperature to obtain a finished high-strength modified PA6 composite material.
2. The method for preparing a high-strength modified PA6 composite material according to claim 1, characterized in that: The high-strength modified PA6 composite material is made of 48-50 parts by weight of PA6 resin, 22-25 parts by weight of PA10T resin, 24-26 parts by weight of a filler composition, 0.8-1.2 parts by weight of an antioxidant, 0.5-1.2 parts by weight of an anti-ultraviolet aging additive, 0.8-1.6 parts by weight of a lubricant, and 1.0-1.5 parts by weight of a coupling agent.
3. The method for preparing a high-strength modified PA6 composite material according to claim 2, characterized in that: The chopped glass fiber with surface grafted nanocarbon includes chopped glass fiber as a carrier, the length of the chopped glass fiber is 0.5-3mm, and at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nanocarbon fibers is grafted on the surface of the chopped glass fiber by in-situ sintering of nanometal.
4. A method for preparing a high-strength modified PA6 composite material according to claim 2 or 3, characterized in that: The inorganic whiskers with surface grafted nanocarbons include inorganic whiskers as carriers, the length of the inorganic whiskers is 0.5-30 μm, and at least one of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and nanocarbon fibers is grafted onto the surface of the inorganic whiskers by in-situ sintering of nanometals.
5. The method for preparing a high-strength modified PA6 composite material according to claim 4, characterized in that: The inorganic whisker is at least one of zinc oxide whisker, zirconium oxide whisker and aluminum oxide whisker.
6. The method for preparing a high-strength modified PA6 composite material according to claim 4, characterized in that: The chopped glass fibers with nano-carbon grafted on the surface are prepared by compounding chopped glass fibers with multi-walled carbon nanotube grafted on the surface and chopped glass fibers with graphene grafted on the surface in a mass ratio of 100:(50-200).
7. The method for preparing a high-strength modified PA6 composite material according to claim 6, characterized in that: The inorganic whisker with nano-carbon grafted on the surface is prepared by compounding the inorganic whisker with multi-walled carbon nanotube grafted on the surface and the inorganic whisker with graphene grafted on the surface in a mass ratio of 100:(50-200).
8. The method for preparing a high-strength modified PA6 composite material according to claim 7, characterized in that: The filler composition is made of the following raw materials in percentage by mass: 30-45 wt% of chopped glass fibers with multi-walled carbon nanotubes grafted on the surface, 50-60 wt% of chopped glass fibers with graphene grafted on the surface, 3-6 wt% of inorganic whiskers with multi-walled carbon nanotubes grafted on the surface, and 2-4 wt% of inorganic whiskers with graphene grafted on the surface.
9. The method for preparing a high-strength modified PA6 composite material according to claim 7, characterized in that: The antioxidant is composed of nano silicon nitride, antioxidant 1010 and antioxidant 168; the anti-ultraviolet aging additive is at least one of UV-234, UV-622, UV-1130, UV-292 and UV-123; the lubricant is at least one of polytetrafluoroethylene powder, molybdenum disulfide and flake graphite; the coupling agent is at least one of isocyanate silane, epoxy silane and titanate coupling agent.
10. The method for preparing a high-strength modified PA6 composite material according to claim 9, characterized in that: The coupling agent is composed of gamma-glycidyloxypropyltrimethoxysilane and tri(dioctylpyrophosphate)titanate isopropyl in a mass ratio of 100:(10-25).
Citation Information
Patent Citations
Low-floating-fiber high-glossiness glass fiber reinforced polyamide composition
CN108676355A
High-thermal conductivity nylon compound material
CN109265986A
Modified PA compound material and production method thereof
CN109971164A
DTY silk yarn and preparation process thereof
CN116180272A
Negative active material, negative plate and lithium ion battery
CN118156438A
Cited By
Bow and arrow supporting composite material and preparation method and application thereof
CN121293743A